PENERAPAN METODE SQC (STATISTICAL QUALITY CONTROL) UNTUK PENINGKATAN KUALITAS PROSES ASSEMBLY SIDM DI PT IEIPENERAPAN METODE SQC (STATISTICAL QUALITY CONTROL) UNTUK PENINGKATAN KUALITAS PROSES ASSEMBLY SIDM DI PT IEI - Santoso, Edi; Fitri, Friyenti (Industrial and Systems Engineering Assessment Journal (INASEA), 2010)
To determine the cause of frequent occurrence of defects required data processing using seven basic tools such as p control chart because the data is attribute data, pareto diagram to see part of the most dominant defect and cause-effect diagram to analyze the causes of disability. From the data processing done for the p control chart produced some printer models appear to be in a state of statistical control. And there are some models that are not in the condition of statistical control as evidenced by the release of some data in the chart control chart p. Pareto diagram can be known from experience that the greatest disability of all models are board games and housing assy lower. While the cause-effect diagrams that most contribute to the causes defect fail part is the part or parts of disability by itself. By looking at the data processing and analysis can be known that the defect that often happens is bad or defective component functions. And to improve the quality of SIDM assembly process in PT. Indonesia EPSON Industry needs to be improved by applying methods of SQC (Statistical Quality Control).